Thermal radiation and chemical reaction effects in second grade fluid flow in the existence of nanoparticles and micro-organisms over a melting surface - Amala Olkha; Mukesh Kumar (Hybrid Advances)
This research endeavour investigates the flow of non-Newtonian second-grade fluid accompanying thermal and mass transport, in the existence of nanoparticles and motile microbes, produced by an inclined, permeable sheet stretching linearly. Impacts of various factors (heat source, chemical reaction, suction/injection, thermophoresis, Brownian movement, slip, etc.) influencing fluid flow, heat and mass transport are invoked in the investigation. Using adequate transformations, the regulating PDEs are transformed into non-dimensional ODEs. The problem is tackled analytically by utilizing HAM and numerically also employing the bvp4c approach on MATLAB. The influence of the affecting parameters that occurred in the problem are depicted graphically on the flow, energy, nanoparticles concentration, and micro-organisms distribution and discussed. It is concluded that the Grashof numbers rises the pace of the flow, while the velocity slip parameter (λ1), angle of inclination (α), porous medium parameter (D) and suction parameter (S) reduce the flow. The impacts of the Brinkman number (Br), radiation parameter (Rd), Brownian motion (Nb), and thermophoresis parameter (Nt) are also found to upsurge the temperature field while opposite effect is observed due to the melting parameter (Me) and temperature slip parameter (λ2). It is also observed that the reaction parameter (Kn), concentration slip parameter (λ3), and Brownian motion (Nb) reduce the concentration profile, while the thermophoresis parameter (Nt) rises the concentration profile. Furthermore, microorganisms profile reduces for increasing values of Lewis number (Lb), Peclet number (Pe), and microorganism slip parameter (λ4). Further, values of skin friction coefficient and temperature gradient presented in tabular form are compared with findings of other researchers and found in a very good match.